(untitled) (Journal of the College of Basic Education, 2022)
The aim of this study is to identify the I.P.A.G.A’s model effectiveness in the Reasoning thinking of the grade three girls’ students’ intermediat stage, and how their academic achievement in mathematics will be. To fullfil this goal, an experimental process with two groups is considered: experimental & control’s group based on the post-test. The sample of study consists of (76) girls students, partitioned into two groups: The first group is the Experimental group with (39) students in which I.P.A.G.A’s model is applied on their learning strategy. While, the second group, the control group which contains (37) students in which the usual way is applied in their learning. The pority Equivalence had been done on both groups by using many variables such as: the chronological age, pre academic achievement in mathematics, their level of intelligence and Reasoning Thinking abilities. To collect the data related to the experiment: both Reasoning Thinking test and achievement test with multiple choices had been formed; consisting of (30) test sections and the calculating test consist of (30) test sections with objective type had been formed. The appropriate statistics analysis for both sections had bee done beside the Psychometric proprieties. According to the result of the experiment, the experimental group shows superiem in achievement and Reasoning thinking that had been teached with I.P.A.G.A model.